The KIPA method for the assessment of land suitability - Schneller, Krisztián; Podmaniczky, László (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
In order to review the regions and determine the land use categories of the National Spatial Plan (NSP), a land- use survey was carried out. This allowed us to conduct a study towards improving the methodology of area function and area suitability analyses. Setting the suitability of lands for arable production as an example, this paper presents the potential of the so-called KIPA-method in the field of land assessment. Being based on experts’ strategies, KIPA is suitable for ranking complex systems. Our KIPA-analysis studied fields (areas) with different environmental variables. The analysis ranked these different areas on the basis of their suitability to the production of various (in this study: five) arable crops. Environmental variables, weighed according to experts’ opinion were the basis of the KIPA-analysis, which involved the composite comparison of the studied areas. In order to evaluate and rank the areas, we calculated the difference between preference (advantage) and incompetence (disadvantage) figures for each area per each environmental variable. The studied areas (area- variables) were classified and evaluated according to their ranking in the before-mentioned analysis. These field studies resulted in helping us to determine what would the qualifications of the rating ‘high-quality arable land’ be in the context of NSP.